Impact of Climate Change on Hydro-Energy Potential A MCDM and Neural Network Approach - Majumder, Mrinmoy; Saha, Apu K. (SpringerBriefs in Energy, 2016)
This Brief presents the impact of climatic abnormalities on hydropower potential of different regions of the World. In this regard, multi-criteria decision making and neural network are used to predict the impact of the change cognitively by an index. The results from the study show that the hydro-energy potential of the Asian region is mostly vulnerable with respect to other regions of the World. The model results also encourage further application of the index to analyse the impact of climate change on potential of hydro-energy.